2019
DOI: 10.1002/oby.22501
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Protein Glycoxidation is Associated with Weight‐Loss Potential

Abstract: Objective This study aimed to characterize the differences in protein oxidation biomarkers in adipose tissue (AT) as an indicator of AT metabolism and bariatric surgery weight‐loss success. Methods A human model, in which sixty‐five individuals with obesity underwent bariatric surgery, and a diet‐induced obesity animal model, in which animals were treated for 2 months with normocaloric diets, were analyzed to determine the associations between AT protein oxidation and body weight loss. Protein oxidative biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In addition, Lasselin et al found that the higher VAT gene expression of IL-10 and M1-macrophage markers before BS predicts poorer BMI reduction after surgery [26]. Both VAT and, in particular, SAT levels of protein glycoxidation have also been directly correlated with WL after BS [27]. Notably, in another study performed only on females, baseline UCP2 and PLIN1 expression in SAT were negatively associated with TBWL at 6 months after surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lasselin et al found that the higher VAT gene expression of IL-10 and M1-macrophage markers before BS predicts poorer BMI reduction after surgery [26]. Both VAT and, in particular, SAT levels of protein glycoxidation have also been directly correlated with WL after BS [27]. Notably, in another study performed only on females, baseline UCP2 and PLIN1 expression in SAT were negatively associated with TBWL at 6 months after surgery [28].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the adipose tissue metabolism, this capacity to reduce body weight could be explained by an improvement in the capacity of glucose metabolism evidenced by higher levels of Irs1 , CEL, and 2SC; and the greater sensitivity to glucose and insulin tolerance tests. This behavior has also been observed in humans, where patients with higher levels of CEL and 2SC in adipose tissue, have a greater capacity for weight reduction after bariatric surgery [11]. About the transcription factors related to mitochondria, based on the PLS-DA analysis soluble fibre treatment was characterized to present the lowest levels of Tfam .…”
Section: Discussionmentioning
confidence: 62%
“…Mitochondrial dysfunction in adipocytes possibly induced by lipotoxicity results in detrimental effects on its differentiation, lipid metabolism, insulin sensitivity, and oxidative capacity between others and has been reported to have a strong correlation with metabolic diseases, including obesity, type 2 diabetes and other metabolic diseases [10]. In this context, adipose tissue “healthy” metabolism is a key feature for the success of weight reduction in patients with morbid obesity after bariatric surgery [11]. Nonetheless, the main problem in this context is how to improve the metabolic capacity of adipose tissue of people with obesity that shows an unbalanced metabolism.…”
Section: Introductionmentioning
confidence: 99%